[OP.8B.01] GENDER DIFFERENCES IN THE METABOLC SYNDROME: HYPERTENSION IS THE FIRST APPARENT COMPONENT IN MEN, WHEREAS INCREASED WAIST CIRCUMFERENCE LEADS IN WOMEN. (September 2017) - Marcus, Y.; Segev, E.; Shefer, G.; Zeid, D.; Shenkerman, G.; Buch, A.; Shenhar, S.; Shapira, I.; Berliner, S.; Stern, N.
Abstract : Objective: The metabolic syndrome consists of several components in a cluster, but the order of their individual appearance has thus far received little attention. Central obesity is believed to be the driving force whereas other components follow as a reflection of obesity-dependent vascular and metabolic anomalies. Aim: To determine the sequential rate of individual components of the metabolic syndrome in a health screening center. Design and method: We analyzed 19, 328 subjects, of whom 13, 953 were presumed healthy with a BMI 19–46 kg/m 2 and no medical treatment. 6548 had none of the components of the metabolic syndrome (MS; MS = 0). Results: Even at the lowest BMI zone of 19Kg/m 2 (n = 325), 16% already had at least one component of the MS. Further, both the number of components and their numerical values rose linearly with BMI: at BMI = 29 kg/m 2, 75% had MS 1 or higher and the number of subjects with 1, 2, 3, 4 or 5 MS (MS1, MS2, MS3, MS4, MS5) components increased as a function of BMI from the leanest to the most obese subjects. There was a gender related dimorphic expression of the order of appearance of the MS components in clusters: in men, hypertension was the leading, most prevalent components when MS component number is low, being present in 32%, 48%, 62%, and 74% of men with MS1, MS2, M3 MS4, respectively. In women, in contrast, central obesity shows the earliest and highest prevalence as it is present in 32%, 74%, 91% and 97% of women with MS1–4, respectively. Stated alternatively, central obesity is the driving force in females (p < 0.01), whereas hypertension precedes central obesity in men in MS component clustering (p < 0.05). Conclusions: Hypertension appears most commonly as the first component of MS in men, whereas in women, waist circumference precedes other MS components. These results suggest that hypertension plays an earlier and perhaps more prominent role in MS in men, whereas in women central obesity is first, thus fitting the traditional concept of the pathogenesis of MS via excess centrally deposited fat.